2011
DOI: 10.1016/j.virol.2011.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of soybean dwarf virus isolates in the eastern United States confirms the presence of both D and Y strains and provides evidence of mixed infections and recombination

Abstract: Soybean dwarf virus (SbDV), first identified as an agricultural problem in Japan, has emerged as a growing problem in the Midwestern United States. The majority of research on SbDV had been limited to four lab maintained strains from Japan. SbDV had been found in clover in the eastern United States, but these isolates rarely emerged into soybeans. These isolates were analyzed by multiplex PCR and sequencing, revealing that some were infections of both Y and D components, including a recombinant subisolate. Phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Isolates of SbDV in the Midwest are D-like and known to infect red clover (11,41), while most isolates found in mid-Atlantic states areY-like or mixed D and Y and found in white clover (7) ( Table I). Isolates obtained from red clover in eastern states (7,28) also were found to be D-like, similar to Midwest isolates. The preference of A. glycines for red clover may be significant in the epidemiology of SbDV since it may serve as an alternative host for SbDV, especially SbDV-D,…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Isolates of SbDV in the Midwest are D-like and known to infect red clover (11,41), while most isolates found in mid-Atlantic states areY-like or mixed D and Y and found in white clover (7) ( Table I). Isolates obtained from red clover in eastern states (7,28) also were found to be D-like, similar to Midwest isolates. The preference of A. glycines for red clover may be significant in the epidemiology of SbDV since it may serve as an alternative host for SbDV, especially SbDV-D,…”
Section: Discussionmentioning
confidence: 61%
“…Isolates were routinely transferred with A. pisum (pea aphid), Myzus persicae (Sulzer) (green peach aphid), and/or Nearctaphis bakeri (Cowen) (short-beaked clover aphid) (7,11). Some isolates closely align with the dwarfing genotype of SbDV-D, some with the yellowing genotype SbDV-Y, and some were coinfected with both genotypes (28). IVansmission experiments.…”
Section: Iviaterials and Methodsmentioning
confidence: 99%
“…In theory, each clone represented a unique viral RNA, and comparing the sequences of the viral clones to the consensus sequence provided a snapshot of the genetic diversity generated within a given viral population. Using these clones as a representative sample of viral populations, mutation frequency and the percentage of mutated viral clones were used as indicators of population diversity (Schneider et al 2011). Control reactions were done using in vitro transcripts as the template RNA to estimate the level of variability introduced by transcription, RT, and thermal cycling.…”
Section: Sbdv Genetic Diversity and Mutation Frequency In Plant Hostsmentioning
confidence: 99%
“…. Soybean aphids and SbDV isolates transmitted by soybean aphids were also discovered in the eastern US (Schneider et al 2011). However, SbDV infections in fields were limited, and only occurred on the very edges of the fields.…”
mentioning
confidence: 99%
“…A survey of soybean diseases in northern Illinois also identified two SbDV-D strains [7]. Recently, the presence of mixed infections of both D and Y strains were confirmed in the eastern United States [8], and several U.S. isolates were found to be transmitted by A. glycines [9] Currently, there are no SbDV resistant commercial cultivars available. More recently, it has been found that the Rsdv1 quantitative trait loci gene was responsible for resistance of an Indonesian cultivar ‘Wilis’ [10], but the mechanism of such gene is still unclear [11].…”
Section: Introductionmentioning
confidence: 99%